2014
DOI: 10.3989/gya.0349141
|View full text |Cite
|
Sign up to set email alerts
|

Oleogels of virgin olive oil with carnauba wax and monoglyceride as spreadable products

Abstract: SUMMARY:The oleogels of virgin olive oil with carnauba wax and monoglyceride were prepared to determine the most suitable spreadable product. The oil binding capacities of monoglyceride oleogels were higher than those of the carnauba wax oleogels. There was no true crystalline structure with carnauba wax at 3%. Although the highest solid fat content was in the 10% monoglyceride oleogel (9.38%), it was 12.15% in the commercial breakfast margarine at 20 °C. The peak melting temperature of the margarine was 47.11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
48
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(54 citation statements)
references
References 25 publications
6
48
0
Order By: Relevance
“…For example, the hardness of the oleogel developed by 12% monostearin at 4°C (701.46 ± 43.45 g) was nearly 8 times higher than that developed by 6% monostearin at 20°C (87.53 ± 9.91 g). According to previous reports, the high dosage structuring agent and low storage temperature could increase the crystallinity degree of structuring agent in oils and strengthen its binding effect on the oils (Davidovich-Pinhas et al, 2015;Öǧütcü & Yılmaz, 2014), which coincided with our results. It was also concluded that the adjustment of texture properties of the lutein ester-loaded oleogels could be achieved by changing the monostearin dosage and cooling temperature to meet different application requirements.…”
Section: Texture Analysissupporting
confidence: 93%
“…For example, the hardness of the oleogel developed by 12% monostearin at 4°C (701.46 ± 43.45 g) was nearly 8 times higher than that developed by 6% monostearin at 20°C (87.53 ± 9.91 g). According to previous reports, the high dosage structuring agent and low storage temperature could increase the crystallinity degree of structuring agent in oils and strengthen its binding effect on the oils (Davidovich-Pinhas et al, 2015;Öǧütcü & Yılmaz, 2014), which coincided with our results. It was also concluded that the adjustment of texture properties of the lutein ester-loaded oleogels could be achieved by changing the monostearin dosage and cooling temperature to meet different application requirements.…”
Section: Texture Analysissupporting
confidence: 93%
“…Many different vegetable oils, such as sunflower oil, soybean oil, corn oil, canola oil, hazelnut oil, rice bran oil, grape seed oil, rapeseed oil, and flaxseed oil have been utilized for oleogel production with the aim to investigate their properties and their potential applications [8]. However, there are only a few studies using olive oil as the only base oil for wax-based oleogel production [9][10][11][12][13][14], whereas the most recent reports have formulated oleogels with a mixture of vegetable oils, including olive oil [15][16][17]. Olive oil oleogels have been formulated to date with the utilization of rice bran wax, carnauba wax, beeswax, and sunflower wax, whereas their physical properties point out their potential application in spreadable fat products, such as breakfast margarine [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…One of the most interesting features is their ability to present gel-like behaviour even using low amounts of gelator molecules (e.g. beeswax; ethyl-cellulose; fatty acid derivatives; oryzanol combined with phytosterols) (Cerqueira et al, 2017;Martins et al, 2016;Öǧütcü and Yılmaz, 2014;Patel, 2015). Previous works reporting on beeswax-based oleogels, demonstrated their ability to structure different types of oil and to incorporate bioactive compounds (Martins et al, 2016;Patel and Dewettinck, 2016).…”
Section: Introductionmentioning
confidence: 99%